195k views
4 votes
Does anyone know how to solve this questions im confused. Thank you so much is you help!

Does anyone know how to solve this questions im confused. Thank you so much is you-example-1
User FZeiser
by
6.0k points

1 Answer

0 votes

Answers:


g(f(\text{x})) = -3\text{x}^2+3


g(f(2)) = -9

=======================================================

Step-by-step explanation:

Let's compute g(f(x))

We do this by starting with the outer function g(x). Then replace every x with f(x). Then plug in the definition of f(x) as shown below.


g(\text{x}) = \text{x}-1\\\\g(f(\text{x})) = f(\text{x})-1\\\\g(f(\text{x})) = 4-3\text{x}^2-1\\\\g(f(\text{x})) = -3\text{x}^2+3\\\\

At this point, we then plug in x = 2 so we can find that...


g(f(\text{x})) = -3\text{x}^2+3\\\\g(f(2)) = -3(2)^2+3\\\\g(f(2)) = -3(4)+3\\\\g(f(2)) = -12+3\\\\g(f(2)) = -9\\\\

User Akraf
by
5.6k points